The investigation of consumer attitude towards Western and Eastern Television advertisements: The perspective of Vietnamese housewives in United Kingdom and Viet Nam - Le, Man Khanh (2016)
Culture study has never failed to arouse arguments and discussions among scholars. Culture is diversified and shapes people minds. Thus, people from different cultures have different attitudes towards a specific issue. On the other hand, people are also seen as influenced entities. Therefore, as a consequence of cultural differences, globalization and television effects, the question whether there is any difference in consumer attitude between those who come from different cultures is posed.